2020
DOI: 10.3386/w28162
|View full text |Cite
|
Sign up to set email alerts
|

Why is End-of-Life Spending So High? Evidence from Cancer Patients

Abstract: The concentration of healthcare spending at the end of life is widely documented but poorly understood. To gain insight, we focus on patients newly diagnosed with cancer. They display the familiar pattern: even among cancer patients with similar initial prognoses, monthly spending in the year post diagnosis is over twice as high for those who die within the year than those who survive. This elevated spending on decedents is almost entirely driven by higher inpatient spending, particularly low-intensity admissi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 0 publications
0
2
0
Order By: Relevance
“…Differences in Medicare spending at the end of life by oncology specialty have not been previously reported. It has been established that cancer care spending increases at the end-of-life, driven mainly by inpatient spending 25 26. Similarly, the majority of our observed differences in Medicare spending at the end of life are due to differences in inpatient spending, with gynecologic oncologist patients having significantly higher Medicare spending.…”
Section: Discussionmentioning
confidence: 55%
See 1 more Smart Citation
“…Differences in Medicare spending at the end of life by oncology specialty have not been previously reported. It has been established that cancer care spending increases at the end-of-life, driven mainly by inpatient spending 25 26. Similarly, the majority of our observed differences in Medicare spending at the end of life are due to differences in inpatient spending, with gynecologic oncologist patients having significantly higher Medicare spending.…”
Section: Discussionmentioning
confidence: 55%
“…Practice patterns may be different for younger patients or those with commercial insurance or Medicare Advantage, which is an alternate insurance plan where Medicare services are subcontracted and overseen by commercial (private) insurers. Studies have found that end-of-life spending25 and palliative care specialist care28 are higher for younger patients and that patients with Medicare Advantage tend to use hospice more and hospital services less at the end of life compared with patients with fee-for-service Medicare 29 30. However, there are data that beneficiaries enrolled in Medicare Advantage do not differ significantly in characteristics compared with those in traditional Medicare 31.…”
Section: Discussionmentioning
confidence: 99%